How can cross-functional integration support the development of resilience capabilities? The case of collaboration in the automotive industry. Issue 6 (22nd May 2020) - Poberschnigg, Tayanne Ferraz da Silva; Pimenta, Marcio Lopes; Hilletofth, Per
Abstract : Purpose: The purpose of this study is to analyze cross-functional integration processes and their respective impacts on resilience capabilities, with particular emphasis on collaboration, in an automotive supply chain. Design/methodology/approach: A case study was conducted in an automotive supply chain through 18 in-depth interviews with managers from six different companies, namely, two suppliers, one focal manufacturer and three customers. The automotive industry is one of the most vital industries in the Brazilian economy and is still recovering from the 2015 financial crisis, making it an interesting case for this research. Findings: The findings reveal several links between resilience and cross-functional integration literatures through the analysis of three basic categories, namely, disruptions (lack of product, interruption of production, delivery delay, organizational bankruptcy and sales loss); capabilities (redundancy, flexibility, adaptability, collaboration, visibility and agility); and integration factors (cross-functional meetings, adequate communication, longevity of relationships, cross-functional training, recognition of interdependence and the consideration given to informal groups). Practical implications: This research addresses several implications for practitioners. Managers should pay attention to the cross-functional teams, which may provide internal collaboration, and hence collaboration in the supply chain. Originality/value: This paper suggests a new concept for the collaboration capability. According to the results, collaboration is the capability of dealing with formal and informal factors to integrate both the internal functions and supply chain members, which can provide visibility, agility and adaptability toward supply chain resilience.